PENGARUH MEDIA PEMBELAJARAN AUDIOVISUAL TERHADAP HASIL BELAJAR SISWA MATERI SEL KELAS XI MIA SMA - Yenni, Yenni; Syamswisna, Syamswisna; Marlina, Reni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This research aimed to find out the effect of audiovisual teaching media of cell on student’s achievement in grade XI of Senior High School (SMA) 6 Pontianak. The research was quasi experimental design using nonequivalent control group design. The sampling technique was used intact group. The study sample was class XI MIA 1 as the experimental group and XI MIA 4 as the control group. The instrument used was multiple choice test consist of 20 items. The research finding showed that the average score of student’s achievement for the experimental group was 15,70 and  for the control group was 12,79. Based on U Mann Whitney test results, obtained Zcount  (-2,61) < -Ztable (-1,96). This meant that there was a significant differences between student’s achievement using audiovisual media and powerpoint media. The effect size score was 0,69 with average category. It shows that learning by using audiovisual media of cell gives effect of 25,49%. Keywords: Effect, audiovisual, cell topic, student’s achievement.